Thoracic endovascular aortic repair (TEVAR) for an acute type A aortic dissection following transcatheter aortic valve replacement (TAVR) - Vy C. Dang, BS; Paul Haddad, MD; Ross G. McFall, MD; Jennifer Klopfenstein, MD; Michael J. Reardon, MD; Maham Rahimi, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
An 86-year-old male with multiple medical comorbidities was referred for an elective transcatheter aortic valve replacement (TAVR) for severe symptomatic aortic stenosis with an ejection fraction of 35%. A self-expanding valve was deployed successfully, but intraoperative transesophageal echocardiography (TEE) confirmed an acute type A aortic dissection (ATAAD), necessitating immediate intervention. Multiple intraoperative imaging modalities were utilized for deployment of a conformable GORE TAG (cTAG) stent graft for thoracic endovascular aortic repair (TEVAR). This case demonstrates TEVAR as an effective, minimally invasive option for immediate repair of ATAAD as a complication of TAVR in a high-risk surgical patient.